Penghapusan Unsur Melawan Hukum dalam Tindak Pidana Korupsi setelah Pengembalian Kerugian Keuangan Negara - Febila Azahra Kayla Fera Widodo (Jurnal Hukum Lex Generalis, 2025)
Corruption is an extraordinary crime that creates systemic impacts on state finances, social justice, and the integrity of public governance. This crime not only causes material losses but also erodes morality, weakens institutions, and undermines citizens’ trust in the rule of law. One of the most debated legal issues concerns the relationship between restitution or the return of state financial losses and the element of “unlawfulness” in corruption offenses. Can the return of losses eliminate this element, or does it merely serve as a mitigating factor during sentencing? This research adopts a normative juridical approach by analyzing statutory provisions, criminal law theories, principles of punishment, academic doctrines, and landmark decisions of the Supreme Court and Constitutional Court. The study concludes that the return of state losses cannot eliminate the element of unlawfulness because corruption is classified as a formal offense, completed once the unlawful act is committed. Restitution may only be considered a mitigating circumstance rather than a justification for criminal exemption. Therefore, restitution must be understood as a legal and moral duty, not as a means to evade accountability. Harmonization of legal regulations and judicial guidelines is essential to ensure that the anti-corruption framework upholds consistency, justice, and deterrence. Firm, transparent, and integrity-based law enforcement is crucial to maintaining the moral foundation of justice and reinforcing public confidence in Indonesia’s legal system.